Pedunculopontine Nucleus Area Oscillations during Stance, Stepping and Freezing in Parkinson’s Disease - Fraix, Valerie; Bastin, Julien; David, Olivier; Goetz, Laurent; Ferraye, Murielle; Benabid, Alim-Louis; Chabardes, Stephan; Pollak, Pierre; Debû, Bettina (PloS one, 2013)
The pedunculopontine area (PPNa) including the pedunculopontine and cuneiform nuclei, belongs to the mesencephalic locomotor region. Little is known about the oscillatory mechanisms underlying the function of this region in postural and gait control. We examined the modulations of the oscillatory activity of the PPNa and cortex during stepping, a surrogate of gait, and stance in seven Parkinson's disease patients who received bilateral PPNa implantation for disabling freezing of gait (FOG). In the days following the surgery, we recorded behavioural data together with the local field potentials of the PPNa during sitting, standing and stepping-in-place, under two dopaminergic medication conditions (OFF and ON levodopa). Our results showed that OFF levodopa, all subjects had FOG during step-in-place trials, while ON levodopa, stepping was effective (mean duration of FOG decreasing from 61.7±36.1% to 7.3±10.1% of trial duration). ON levodopa, there was an increase in PPNa alpha (5-12 Hz) oscillatory activity and a decrease in beta (13-35 Hz) and gamma (65-90 Hz) bands activity. PPNa activity was not modulated during quiet standing and sitting. Our results confirm the role of the PPNa in the regulation of gait and suggest that, in Parkinson disease, gait difficulties could be related to an imbalance between low and higher frequencies.